2011
DOI: 10.1042/bst0390813
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-free purification of membrane proteins with intact native membrane environment

Abstract: In order to study the structure and function of a protein, it is generally required that the protein in question is purified away from all others. For soluble proteins, this process is greatly aided by the lack of any restriction on the free and independent diffusion of individual protein particles in three dimensions. This is not the case for membrane proteins, as the membrane itself forms a continuum that joins the proteins within the membrane with one another. It is therefore essential that the membrane is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 21 publications
0
89
0
1
Order By: Relevance
“…This has opened options to purify membrane proteins that are unstable in detergent micelles and to study native protein-lipid interactions by biochemical methods. A further advantage of these so-called native nanodisks is that they are small, with sizes in the range of 10-25 nm (4)(5)(6)(9)(10)(11)(12)(13)(14)(15). This makes them suitable to be characterized by a variety of biophysical approaches including UV/Vis-and fluorescence spectroscopy (5,6,8), as well as light scattering techniques (6,14).…”
Section: Introductionmentioning
confidence: 99%
“…This has opened options to purify membrane proteins that are unstable in detergent micelles and to study native protein-lipid interactions by biochemical methods. A further advantage of these so-called native nanodisks is that they are small, with sizes in the range of 10-25 nm (4)(5)(6)(9)(10)(11)(12)(13)(14)(15). This makes them suitable to be characterized by a variety of biophysical approaches including UV/Vis-and fluorescence spectroscopy (5,6,8), as well as light scattering techniques (6,14).…”
Section: Introductionmentioning
confidence: 99%
“…Here we report the application of a recently developed system for detergent-free extraction of ABC transporters from their native membranes using a readily available, biocompatible and chemically stable polymer, polystyrene-co-maleic acid (SMA) [17][18][19]. The polymer inserts into the membrane isolating small discs of lipid bilayer that are encircled by the polymer, termed SMA lipid particles (SMALPs) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Such reconstitution is not straightforward however, especially because of the high affinity of SMA for lipids, which complicates their removal and may impair the formation of extended bilayers. It has been suggested that lowering the pH would solve this problem (Jamshad et al 2011). However, in our hands this approach was not successful (Koorengevel, Scheidelaar and Dörr, unpublished observations).…”
Section: Applications Of Native Nanodiscs and New Possibilities Offermentioning
confidence: 71%